Faktor-Faktor yang Mempengaruhi Tingkat Kesejahteraan Nelayan Jaring Rampus (Bottom Gill Net) di Pelabuhan Perikanan Pantai (PPP) Bondet Kabupaten Cirebon, Jawa Barat - Evi Susilawati (Barakuda'45, 2021)
Bondet Coastal Fishery Port (PPP) is located in Cirebon Regency, which is adjacent to Grogol Village, Gunung Jati District, Cirebon Regency, where Grogol Village is one of the villages as a center for fishing fishermen with fishing gear mostly rampus nets. The rampus net (bottom gill net) is one of the fishing gear that can generate a source of income for fishermen in Grogol Village, Gunungjati District, Cirebon Regency which can be operated and produce fish almost every month. The purpose of this study is to explain the welfare of fishermen which can be analyzed in terms of income and expenditure. Bottom gill net fishermen. The method used in this research is descriptive method. This study uses a survey technique, which is a way of collecting data from a number of units or individuals at the same time. The data obtained were analyzed through financial analysis of the fishing business using rampus nets at the Coastal Fishery Port (PPP) Bondet, Cirebon Regency. The results showed that there was income inequality among Bottom Gill Net fishermen in Grogol village with a Gini coefficient value (inequality) of 0.24. Based on welfare indicators, according to BPS and the results of the summation of scores, it is known that bottom gill net fishermen in Grogol village have a high level of welfare (scores 20-24) with a total score of 23, and based on statistical analysis using NTN, the NTN value for bottom gill net fishermen in Grogol village is equal to 9,6 %, where NTN > 1, it can be stated that all Bottom Gill Net fishermen respondents are prosperous. There is no difference in the final result of the level of welfare according to BPS and NTN.